Validity of the Katz Index to assess activities of daily living by informants in neuropathological studies - Renata Eloah de Lucena Ferretti-Rebustini; Marcos Alencar Abaide Balbinotti; Wilson Jacob-Filho; Flávio Rebustini; Claudia Kimie Suemoto; Carlos Augusto Gonçalves Pasqualucci; José Marcelo Farfel; Renata Elaine Paraizo Leite; Lea Tenenholz Grinberg; Ricardo Nitrini (SciELO, 2015)
Abstract OBJECTIVE To analyze the evidences of construct validity of the Katz Index for the retrospective assessment of activities of daily living (ADL) by informants, to assist neuropathological studies in the elderly. METHOD A cross-sectional study analyzed the functional ability of ADL measure by the Katz Index, of 650 cases randomly selected from the Brazilian Brain Bank of the Ageing Brain Study Group (BBBABSG) database. Sample was divided in two subsamples for the analysis (N=325, each) and then stratified according to cognitive decline assessed by the Clinical Dementia Rating Scale (CDR). Factor analyses with calculations of internal consistency and invariance were performed. RESULTS Factor analysis evidenced a unidimensional instrument with optimal internal consistency, in all subgroups. Goodness of fit indices were obtained after two treatments of covariance, indicating adequacy of the scale for assessing ADL by informants. The scale is invariant to cognitive decline meaning that it can be used for subjects with or without cognitive impairment. CONCLUSION Katz Index is valid for the retrospective assessment of basic ADL by informants, with optimal reliability.